Implementation of Tensorflow in the CCTV-Based People Counter Application at PT Matahari Department Store, Tbk - Kusno Prasetya; Arnold Aribowo; Alfa Satyaputra; Jocelyn Olivia (IAIC Publishing, 2020)
Counting the number of visitors (people counter) is an activity carried out in many retail stores. This information, although very simple and basic, can be used as one of the main bases for making decisions. In the past, PT Matahari Department Store, Tbk (MDS) has calculated the number of visitors manually with an accuracy of around 90%. The purpose of this research is to design an automated people counter system using the existing CCTV video networks in MDS stores. The research methodology used is data collection methods in the form of literature studies and interviews, and systems development methods in the form of prototyping. The system uses Tensorflow to recognize visitors who enter and leave the store. This system is a prototype and is used as a proof of concept for MDS to make decisions regarding the application of appropriate technology in carrying out the people counter process along with the things that need to be prepared if this system is to be implemented thoroughly in all MDS stores in Indonesia.